Thyroid Hormone Sensitizes the Imprinting-Associated Induction of Biological Motion Preference in Domestic Chicks - Miura, Momoko; Aoki, Naoya; Yamaguchi, Shinji; Homma, Koichi J.; Matsushima, Toshiya (Frontiers in Physiology, 2018)
Filial imprinting is associated with induction of predisposed preference to animations that bear visual features of Johansson’s biological motion (BM), and the induction is limited to a few days after hatching. As thyroid hormone (3,5,3'-triiodothyronine, T3) plays a critical role in determining the sensitive period of imprinting, we examined if exogenously applied T3 (or iopanoic acid, IOP; a selective inhibitor for converting enzymes) could also sensitize (or desensitize) the BM induction. Chicks were trained by using a non-BM stimulus (rotating red toy) for 2 hours according to a conventional imprinting procedure. Thirty min later, trained chicks were tested for preference to a point-light BM animation (walking chick) over a non-BM animation (linear motion; namely BM score), and for the preference for the familiarized stimulus (red toy) over an unfamiliar one (yellow toy; namely imprinting score). In 1-day chicks, those injected with IOP showed significantly lower scores than controls on both BM and imprinting tests. In 4-days chicks, those injected with T3 showed higher scores than control, but the difference in BM score was not significant. When data from these 4 groups were merged, effect of the interaction (T3 x imprinting score) proved to contribute significantly to the BM score. Imprinting and the accompanying T3 surge may be necessary for the predisposed BM preference to appear in 1-day chicks. Even after the conventional sensitive period is over, exogenous T3 can re-sensitize the BM preference as it does imprinting.